Analysis Of Financial Distress with The Altman Z-Score Method in Food Franchise Companies - Rasyidah, Afifah Putri; Safitri, Teti Anggita (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The Covid-19 pandemic that occurred in Indonesia required the government to take steps by imposing policies during the pandemic. Applicable policies such as the enactment ot the large-scale social restriction policy (PSBB), the imposition of restrictions in community activities (PPKM). This gave rise to a phenomenon during the pandemic that occurred in companies, especially food franchises. Phenomenon that occurs such as the closing of food aotlets in transit areas, shopping centers, and there are even companies that take to the streets to sell their products at relatively affordable prices. As a result of this phenomenon, there are many issues circulating that food franchise companies are experiencing financial distress. This study aims to determine whether a food franchise company is experiencing financial distress by analiysis it is using the Altman Z-score method. This study uses a descriptive quantitative approach, the samples used are 3 food franchise companies. Data collection technidues using literature and documentation. The analysis technique was carried out using the altman Z-score method. The calculation result of the Z score using the Altman method state that food franchise companies are in a state of distress and declining income. The result of this study state that food franchise companies are experiencing financial distress and there is a risk of bankruptcy. This reserch is also a warning for companies in improving financial performance in the future, so that bankruptcy does not occur.